2015
DOI: 10.1002/adma.201504438
|View full text |Cite
|
Sign up to set email alerts
|

Ultrarobust Transparent Cellulose Nanocrystal‐Graphene Membranes with High Electrical Conductivity

Abstract: Ultra-robust nanomembranes possessing high mechanical strength combined with excellent stiffness and toughness rarely achieved in nanocomposite materials are presented. These are fabricated by alternately depositing 1D cellulose nanocrystals and 2D graphene oxide nanosheets by using a spin assisted layer-by-layer assembly technique. Such a unique combination of 1D and 2D reinforcing nanostructures results in layered nanomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
231
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(240 citation statements)
references
References 59 publications
(67 reference statements)
2
231
1
Order By: Relevance
“…Recently, some high-performance GANs have been constructed through the synergistic toughening of 1D nanofibrils, including cellulose nanocrystal (CNC), [170,171] NFC, [140] and CNTs, [141] etc. For example, Wen et al [170] utilized CNC to induce synergistic toughening effect with GO nanosheets, resulting in ultrastrong and highly conductive GANs.…”
Section: One Dimensional Nanofibrilmentioning
confidence: 99%
“…Recently, some high-performance GANs have been constructed through the synergistic toughening of 1D nanofibrils, including cellulose nanocrystal (CNC), [170,171] NFC, [140] and CNTs, [141] etc. For example, Wen et al [170] utilized CNC to induce synergistic toughening effect with GO nanosheets, resulting in ultrastrong and highly conductive GANs.…”
Section: One Dimensional Nanofibrilmentioning
confidence: 99%
“…Other 1D building blocks, such as cellulose nanocrystals (CNCs) [90] and nanofibrillar celluloses, [91,92] can also be introduced to construct a synergistic effect in bioinspired nanocomposites. Recently, Xiong et al [90] reported an ultra-stiff ternary bioinspired nanocomposite by assembling GO nanosheets and polyethyleneimine (PEI)-modified CNCs.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
“…Recently, Xiong et al [90] reported an ultra-stiff ternary bioinspired nanocomposite by assembling GO nanosheets and polyethyleneimine (PEI)-modified CNCs. This ternary nanocomposite possessed a high tensile strength of 655 MPa and a record elastic modulus of 169 GPa.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
“…Recently, different surface treatment strategies were explored to enhance the interface properties between nanofillers and polymer matrices . One of the most attractive strategies is the use of silane‐based coupling agents to enhance the interfacial bonding between nanowhiskers and PLA .…”
Section: Introductionmentioning
confidence: 99%